Interaction of the cyclic-di-GMP binding protein FimX and the Type 4 pilus assembly ATPase promotes pilus assembly - Jain, Ruchi; Sliusarenko, Oleksii; Kazmierczak, Barbara I. (PLoS pathogens, 2017)
Type IVa pili (T4P) are bacterial surface structures that enable motility, adhesion, biofilm formation and virulence. T4P are assembled by nanomachines that span the bacterial cell envelope. Cycles of T4P assembly and retraction, powered by the ATPases PilB and PilT, allow bacteria to attach to and pull themselves along surfaces, so-called "twitching motility". These opposing ATPase activities must be coordinated and T4P assembly limited to one pole for bacteria to show directional movement. How this occurs is still incompletely understood. Herein, we show that the c-di-GMP binding protein FimX, which is required for T4P assembly in Pseudomonas aeruginosa, localizes to the leading pole of twitching bacteria. Polar FimX localization requires both the presence of T4P assembly machine proteins and the assembly ATPase PilB. PilB itself loses its polar localization pattern when FimX is absent. We use two different approaches to confirm that FimX and PilB interact in vivo and in vitro, and further show that point mutant alleles of FimX that do not bind c-di-GMP also do not interact with PilB. Lastly, we demonstrate that FimX positively regulates T4P assembly and twitching motility by promoting the activity of the PilB ATPase, and not by stabilizing assembled pili or by preventing PilT-mediated retraction. Mutated alleles of FimX that no longer bind c-di-GMP do not allow rapid T4P assembly in these assays. We propose that by virtue of its high-affinity for c-di-GMP, FimX can promote T4P assembly when intracellular levels of this cyclic nucleotide are low. As P. aeruginosa PilB is not itself a high-affinity c-di-GMP receptor, unlike many other assembly ATPases, FimX may play a key role in coupling T4P mediated motility and adhesion to levels of this second messenger.